A Pilot Study in Southern Region Primary School: Are Design and Technology Teachers Ready to Teach Programming? - Salleh Hudin, Salmiah (Online Journal for TVET Practitioners, 2024)
This is a pilot study on the teachers’ competency in teaching programming education in primary schools. In response to the growing demand for professionals in the field of computer science, many countries have started to promote programming to young students. Malaysian education also in line with this change. Programming education in primary schools can be highly beneficial for kids as it can develop their logical thinking, creativity, and problem-solving skills. The implementation of an effective programming education needs teachers with good competency. The aspect of competence intended in this study refers to 3 elements in KSA Model which consist of knowledge, skills, and attitude. A quantitative survey was employed to explore the competency of primary school Design and Technology (D&T) teachers in programming. The data was gathered through Google Form online survey. The survey was announced through programming workshop called “Scratch for All” held in Universiti Teknikal Malaysia (UTEM), Melaka. The teachers involved are from 46 schools across three southern Malaysian states, Melaka, Negeri Sembilan, and Johor. As the purpose of this pilot study is to verify the items in questionnaire, the result obtained showed that the items for programming knowledge among D&T teachers had a reliability index of = 0.903, the programming skills items were at = 0.945, and the items measuring teachers' attitudes towards programming were at = 0.933. All the result showed a good determining factor for the planned study. As conclusion, all items in sections (b), (c), and (d) can be used in the planned study to identify the competency of D&T teachers regarding the teaching of programming in primary schools.